2013
DOI: 10.1111/nmo.12121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traumatic brain injury on intestinal contractility

Abstract: Background Patients with traumatic brain injury (TBI) often suffer from gastrointestinal dysfunction including intolerance to enteral feedings. However, it is unclear how TBI affects small intestinal contractile activity. The purpose of this study was to determine if TBI affects intestinal smooth muscle function. Methods Sprague–Dawley rats were subjected to controlled cortical impact injury (TBI). Sham animals underwent a similar surgery but no injury (SHAM). Animals were sacrificed 1, 3, and 7 days after T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 44 publications
(54 reference statements)
1
55
0
2
Order By: Relevance
“…Functionally, decreased contractility of the smooth muscle within the GI tract results in delayed transit times following TBI 108,109 . Pre-clinical data suggests that this functional impairment is correlated with both increased systemic inflammation in the gut and brain atrophy 108 .…”
Section: Top-down: Brain-to-gutmentioning
confidence: 99%
“…Functionally, decreased contractility of the smooth muscle within the GI tract results in delayed transit times following TBI 108,109 . Pre-clinical data suggests that this functional impairment is correlated with both increased systemic inflammation in the gut and brain atrophy 108 .…”
Section: Top-down: Brain-to-gutmentioning
confidence: 99%
“…Some studies showed that moderate TBI with no substantial mucosal damage causes a delayed significant decrease in intestinal contractile activity that occurs primarily in the ileum due to decreased contraction amplitude. In addition, intestinal transit was decreased after TBI [33]. Also, studies demonstrated that TBI induces a decrease in both intestinal contractility and transit and an increase in inflammation in the intestinal smooth muscle suggesting that motility is inhibited in the small intes- tine due to inflammatory damage secondary to the brain injury.…”
Section: Tbi and Gi Problemsmentioning
confidence: 91%
“…Altered contractile activity and motility in the small intestine were associated with increased inflammation in the intestinal smooth muscle [33].…”
Section: Tbi and Gi Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are supported by Spodniewska et al (12) who considered their patients were constipated if they failed to open their bowels for 3 continuous days. While, Olsen et al (13) commented that traumatic patients usually have gastrointestinal dysfunction especially enteral feeding intolerance. Moreover, Nassar et al (1) stated that constipation is occurred in the majority of their studied patients with no significance in terms of age, sex and admission diagnosis.…”
Section: Discussionmentioning
confidence: 99%